Trends of Obesity in 10-Years of Follow-up among Tehranian Children and Adolescents: Tehran Lipid and Glucose Study (TLGS) - Farhad HOSSEINPANAH; Sara SERAHATI; Maryam BARZIN; Shayan ARYANNEZHAD; Maryam REZAIE; Majid VALIZADEH; Fereidoun AZIZI (Tehran University of Medical Sciences, 2019)
Background: We aimed to investigate the trend of childhood obesity in Tehranian population during a median follow-up of 10 years. Methods: Within a prospective cohort study, using data collected from Tehran Lipid and Glucose Study (TLGS), 1406 participants, aged 3-11 yr were selected and monitored in 4 phases: phase I (1999-2001), phase II (2002-2005), phase III (2006-2008) and phase IV (2009-2011). Results: Total prevalence of obesity in children increased from 5.5% to 9.4% from phase I to IV. Performing GEE (Generalized Estimating Equation) analysis, relative risk of obesity was calculated, comparing each phase to its previous phase: phase II in reference to phase I (RR=1.06, CI=1.04-1.08), phase III in reference to phase II (RR=1.01, CI=1.00-1.03) and phase IV in reference to phase III (RR=0.96, CI=0.94-0.98). Between group difference was significant in all subgroups (age, gender, parental obesity) except parental education. Test of interaction for effect of time was insignificant in all subgroups except for the age group. For children younger than 7 yr old at phase I, trend of obesity throughout the study was higher compared to those with 7 yr of age and older at phase I. Conclusion: During a decade of follow-up, trend of obesity was rising in this Tehranian children in both genders, especially in younger children. Any preventive interventions for stopping this trend should focus on early stages of childhood.